Milk Composition for Admixed Dairy Cattle in Tanzania - Cheruiyot, Evans K.; Bett, Rawlynce C.; Amimo, Joshua O.; Mujibi, Fidalis D. N. (Frontiers in Genetics, 2018)
Abstract It is well established that milk composition is affected by the breed and genotype of a cow. The present study investigated the relationship between the proportion of exotic genes and milk composition in Tanzanian crossbred dairy cows. Milk samples were collected from 209 animals kept under smallholder production systems in Rungwe and Lushoto districts of Tanzania. The milk samples were analyzed for the content of components including fat, protein, casein, lactose, solids-not-fat (SNF) and the total solids (TS) through infrared spectroscopy using Milko-Scan FT1 analyzer, (Foss Electric, Denmark). Hair samples for DNA analysis were collected from individual cows and breed composition determined using 150,000 Single Nucleotide Polymorphism (SNP) markers. Cows were grouped into four genetic classes based on the proportion of exotic genes present: 25-49%, 50-74%, 75-84% and > 84%, to mimic a backcross to indigenous zebu breed, F1, F2 and F3 crosses, respectively. The breed types were defined based on international commercial dairy breeds as follows: RG (Norwegian Red X Friesian, Norwegian Red X Guernsey, Norwegian Red X Jersey crosses); RH (Norwegian Red X Holstein crosses); RZ (Norwegian Red X Zebu, Norwegian Red X N'Dama crosses); and ZR (Zebu X GIR, Zebu X Norwegian Red, Zebu X Holstein crosses). Results obtained indicate low variation in milk composition traits between genetic groups and breed types. For all the milk traits except milk total protein and casein content, no significant differences (p < 0.05) were observed among genetic groups. Protein content was significantly (p < 0.05) higher for genetic group 75-84% at 3.4±0.08% compared to 3.18±0.07% for genetic group >84%. Casein content was significantly lower for genetic group >84% (2.98±0.05%) compared to 3.18±0.09% and 3.16±0.06% for genetic group 25-49% and 75-84%, respectively (p < 0.05). There was no significant difference (p < 0.05) between breed types with respect to milk composition traits. These results suggest that selection of breed types to be used in smallholder systems need not pay much emphasis on milk quality differences as most admixed animals would have similar milk composition profiles. However, a larger sample size would be required to quantify any meaningful differences between groups.